Monitoring of different factor VIII replacement products using a factor VIII one‐stage clotting assay on cobas t 511/711 analysers. Issue 6 (30th September 2021) - Ketteler, Carolin; Hoffmann, Ingrid; Davidson, Simon; Tiede, Andreas; Richter, Nina
Abstract: Introduction: Recombinant coagulation factor VIII (FVIII) products are the standard of care for patients with haemophilia A. The development of modified FVIII products has provided benefit for patients but presented challenges for monitoring FVIII activity. Aim: This single‐centre study evaluated the Roche FVIII one‐stage clotting assay (OSA) in measuring FVIII activity in plasma samples spiked with seven FVIII products at clinically relevant concentrations. Methods: FVIII‐deficient plasma samples were spiked with two batches of recombinant FVIII products (octocog alfa, moroctocog alfa, simoctocog alfa, efmoroctocog alfa, damoctocog alfa pegol, rurioctocog alfa pegol, lonoctocog alfa) at 1–120 IU/dL FVIII activity, according to their labelled potency. Measurement was conducted on the cobas t 511/711 analysers using the Roche FVIII OSA and the Technoclone TECHNOCHROM FVIII:C chromogenic substrate assay (CSA). Results: Using the OSA, FVIII activity was close to labelled potency for most analysed FVIII products including a recombinant FVIII Fc fusion protein. PEGylated FVIII product, damoctocog alfa pegol, was marginally above and single‐chain product, lonoctocog alfa, below the predefined acceptance criteria: for FVIII activity < 25 IU/dL: ± 5 IU/dL; for FVIII activity ≥ 25 IU/dL: ± 20% (relative). The different principles of OSA and CSA led to discrepancies in the estimation of all analysed FVIII products. Additionally, in vitro recovery was increased at lower levels of FVIII activity using the OSA, whereas recovery was more consistent using the CSA. Conclusion: These data allow the interpretation of FVIII activity results for different FVIII products using the Roche FVIII OSA on the cobas t 511/711 analysers.